2018
DOI: 10.1007/s10903-018-0723-8
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Unmet Health Needs Among Refugees in Omaha, Nebraska

Abstract: This study assessed the association between acculturation and unmet health needs among refugees. Based on data from the Refugee Health Needs Assessment Survey (n = 291) recently conducted in Omaha, Nebraska, Chi square tests and multivariate logistic regressions were estimated to examine how acculturation among refugees was related to their unmet health needs. Relative to refugees who had been in the U.S. for less than 3 years, refugees who had been in the U.S. for 3-5 years were more likely to report lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…
R efugees in the United States face multiple unique challenges related to acculturation, meeting basic needs, and accessing vital services such as health care [1]. Structural and contextual factors, such as "othering" and discrimination, are potential pathways through which acculturation can erode the health of refugees and their descendants [2].
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
R efugees in the United States face multiple unique challenges related to acculturation, meeting basic needs, and accessing vital services such as health care [1]. Structural and contextual factors, such as "othering" and discrimination, are potential pathways through which acculturation can erode the health of refugees and their descendants [2].
…”
mentioning
confidence: 99%
“…Structural and contextual factors, such as "othering" and discrimination, are potential pathways through which acculturation can erode the health of refugees and their descendants [2]. Although experiences of trauma, displacement, and disruptions in health care are not unique to refugees, the experience of real or threatened danger is a defining characteristic of this population, and traumatic experiences may directly contribute to suboptimal acculturation, health care access, and health outcomes [3].Difficulties in health care access upon arrival in the United States include barriers to navigating complex medical and insurance systems, overcoming language and cultural barriers, institutional mistrust, and the residual impacts of trauma and challenging experiences prior to and during migration [1,4]. These challenges exacerbate health inequities and place families and individuals with refugee status at undue risk for numerous health issues.The barriers to health care faced by newly arrived refugees may be particularly challenging for children, who may fail to receive preventive care, lack proper nutrition, and experience developmental delays, all of which may be due to the often chaotic resettlement process and delayed access to care upon arrival in the United States [5].…”
mentioning
confidence: 99%
“…At six to eight months, cash assistance from the government typically ends as does support from the resettlement agency based on the expectation that refugees are self-sufficient after six to eight months of support 2,3. A study evaluating unmet needs of refugees demonstrated that refugees in the U.S. for a longer period of time are more likely to report a lack of health insurance coverage and a delay in seeing a healthcare provider 22. Policymakers should consider extending Refugee Medical Assistance beyond the first eight months as an additional strategy to improve access to health insurance and ensure stable access to care.…”
Section: Discussionmentioning
confidence: 99%
“…Prior analyses have examined how resettled refugees seek care (noting limited long-term follow-up), barriers to accessing services (including language and the complexity of U.S. systems), and insurance coverage dispar-ities (some estimates exceeding 40% uninsured). [4][5][6] Yet, these analyses have been limited in geographic scope and populations included. Updating these analyses is also critical given the ever-evolving refugee context.…”
Section: Introductionmentioning
confidence: 99%